The geographic distribution of Burkholderia pseudomallei in selected Malaysian locales and its effect on human exposure in changing land use - Abdul Karim Russ, bin Hassan (Universiti Malaysia Sarawak, (UNIMAS), 2012)
The aim of the study was to detect environmental sources of Burkholderia pseudomallei that cause melioidosis and to compare by molecular methods the environmental isolates with clinical isolates from endemic areas of Sarawak. The study was undertaken in view of reported cases of melioidosis from various government hospitals in Sarawak.